Electrolytic etching solution for metallographic structure of cobalt and cobalt-based alloy and metallographic etching method thereof

By using electrolytic corrosion solution of perchloric acid, benzotriazole and anhydrous ethanol, combined with precise electrolytic parameter control, the problem of unclear metallographic structure of cobalt and its alloys in traditional methods is solved, and efficient and accurate metallographic corrosion is achieved, and observation quality and accuracy are improved.

CN119555469AActive Publication Date: 2025-03-04GRIKIN ADVANCED MATERIALS
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510090387.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-04
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

When traditional metallographic display methods deal with cobalt and its alloys, especially high-purity cobalt and its alloys with complex composition or fine grains, the corrosion rate is fast and difficult to operate, which can easily lead to excessive corrosion or unclear display problems, affecting the observation and analysis accuracy of metallographic structure.

Method used

The electrolytic corrosion solution composed of perchloric acid, benzotriazole and anhydrous ethanol is used to accurately proportion and control electrolytic parameters to achieve efficient and accurate electrolytic corrosion of the metallographic structure of cobalt and cobalt-based alloy materials.

Benefits of technology

This method can clearly show the microstructure characteristics of the material, avoid over-corrosion or insufficient corrosion, improve the observation quality and accuracy of metallographic structure, and maintain a good corrosion effect within the temperature range of 0-60℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119555469A_ABST
    Figure CN119555469A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metallographic corrosion, in particular to metallographic structure electrolytic corrosion liquid of cobalt and cobalt-based alloy and a metallographic corrosion method of the metallographic structure electrolytic corrosion liquid. The cobalt and cobalt-based alloy metallographic structure electrolytic corrosion liquid comprises perchloric acid, benzotriazole and absolute ethyl alcohol. The volume ratio of the perchloric acid solution to the saturated benzotriazole ethanol solution to the absolute ethyl alcohol is (20-30): (0.2-0.5): (69.5-79.8), the concentration of the perchloric acid solution is 70-72%, and efficient and accurate electrolytic corrosion of the metallographic structure of the cobalt and cobalt-based alloy material is achieved. The corrosive liquid not only can clearly show the microstructure characteristics of the material, but also can effectively avoid the phenomenon of over-corrosion or insufficient corrosion, thereby greatly improving the observation quality and accuracy of the metallographic structure. The corrosion effect of the corrosive liquid is slightly influenced by temperature, and the good corrosion effect can be achieved at 0-60 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallographic corrosion, and in particular to an electrolytic corrosion solution for metallographic structures of cobalt and cobalt-based alloys and a metallographic corrosion method thereof. Background Art

[0002] Cobalt and its alloys play an irreplaceable role in many high-tech fields such as aerospace, electronic communications, and mechanical manufacturing due to their excellent ferromagnetism, electrical conductivity, and corrosion resistance. With the rapid development of science and technology, the requirements for material performance in these fields are increasing, prompting researchers to conduct more in-depth and detailed research on the microstructure of cobalt and its alloys. The observation and analysis of metallographic structure, as an important means to explore material properties, is of decisive significance for the progress of materials science due to its accuracy and reliability.

[0003] However, the traditional metallographic display method faces many challenges when processing cobalt and its alloys, especially high-purity cobalt and its alloys with complex components or fine grains. The patent document with application number CN201210441849.3 discloses a metallographic erosion method for displaying cobalt-chromium alloy structure, in which aqua regia is used as a corrosive liquid. The patent document with application number CN201110396245.7 discloses a metallographic structure electrolyte, a cobalt corrosion method and a metallographic structure display method thereof, in which a mixed solution of ethanol, n-butanol, water, nitric acid and hydrofluoric acid is used as a corrosive liquid. In actual operation, when directly using aqua regia or a mixed corrosive liquid such as ethanol, n-butanol, nitric acid and hydrofluoric acid to process cobalt or cobalt alloys, the corrosion rate is fast and the operation is difficult, which often leads to excessive corrosion of the material structure or unclear display problems, especially when processing cobalt-based alloys with fine grains or complex components, the phenomenon of incomplete or over-corroded grain display often occurs, which seriously affects the observation and analysis accuracy of the metallographic structure. At the same time, the corrosion effect of the above-mentioned corrosive liquid is significantly affected by the external temperature, and the corrosion success rate is difficult to guarantee.

[0004] In addition, the traditional etching fluid has complex ingredients and contains harmful substances, such as strong acids, which pose a potential threat to the experimental environment and the safety of operators. During the experiment, operators need to contact and handle these harmful substances, which increases health risks, and the discharge and treatment of etching fluids also burden the environment. Summary of the invention

[0005] In view of the problems in the above-mentioned prior art that the corrosion rate is fast and the corrosion effect is significantly affected by temperature, the present invention provides a metallographic structure electrolytic etching solution of cobalt and cobalt-based alloys and a metallographic etching method thereof, using perchloric acid, benzotriazole and anhydrous ethanol as the electrolytic etching solution, utilizing the strong oxidizing and corrosive properties of perchloric acid to corrode the metal, and utilizing benzotriazole as a corrosion inhibitor to slow down the corrosion process.

[0006] To achieve the above object, the technical solution of the present invention is as follows: A metallographic electrolytic etching solution for cobalt and cobalt-based alloys comprises perchloric acid, benzotriazole and anhydrous ethanol; the volume ratio of the perchloric acid solution, the saturated benzotriazole ethanol solution and the anhydrous ethanol is (20-30): (0.2-0.5): (69.5-79.8), and the concentration of the perchloric acid solution is 70-72%.

[0007] Furthermore, the purity of the anhydrous ethanol is ≥99%.

[0008] The present invention also includes the following technical solutions: A metallographic etching method using the above-mentioned metallographic structure electrolytic etching solution of cobalt and cobalt-based alloy comprises the following steps: (1) Cut a cobalt or cobalt-based alloy sample of appropriate size to be observed, grind the sample step by step using silicon carbide sandpaper, and then polish the sample using diamond polishing agent; (2) Adding a metallographic electrolytic corrosion solution of cobalt and cobalt-based alloy into an electrolytic cell, placing the polished sample into the electrolytic corrosion solution, stirring, and connecting a DC power supply for electrolytic corrosion. The voltage of the electrolytic corrosion is 12-14 V, the corrosion time is 20-30 s, and the temperature is 0-60°C; (3) Rinse the corroded sample, blow dry with cold air or dry in an oven, and observe it using a metallographic microscope.

[0009] Furthermore, in step (1), 600, 1000, and 2000 mesh silicon carbide sandpapers are used for step-by-step grinding.

[0010] Furthermore, in step (1), the sample is polished using a diamond polishing agent with a coarseness of 1-1.5 μm, the polishing time is 5-10 min, and the polishing speed is 200-300 r / min.

[0011] Furthermore, in step (2), the stirring speed is 2-5 r / s.

[0012] The reaction mechanism involved in the present invention is as follows: Perchloric acid has strong oxidizing and corrosive properties, and can effectively remove oxides and impurities on the metal surface and corrode the metal. As a corrosion inhibitor, benzotriazole can form a protective film on the metal surface, effectively slow down the corrosion process, protect the material surface, and prevent excessive corrosion. Moreover, the corrosion inhibition effect of benzotriazole is more significant at high temperatures. The corrosion inhibition mechanism of benzotriazole is as follows: benzotriazole is a nitrogen-containing organic heterocyclic compound, which exhibits excellent reactivity and stability due to its unique nitrogen heterocyclic ring in its molecular structure. The nitrogen atom in the benzotriazole molecule carries a lone pair of electrons and can interact with the metal ions on the metal surface, thereby forming a dense protective film on the metal surface, effectively inhibiting the corrosion process. At the same time, the nitrogen heterocyclic structure of benzotriazole gives it high thermal stability, enabling it to maintain the integrity of the molecular structure under high temperature environment, maintain the uniform corrosion of the electrolyte on the material surface, and effectively prevent the deformation of the tissue caused by excessive erosion, which has significant advantages in corrosion protection applications under high temperature environment.

[0013] Compared with the prior art, the present invention has the following beneficial effects: The invention provides a metallographic structure electrolytic etching liquid of cobalt and cobalt-based alloy and a metallographic etching method thereof. By accurately proportioning a perchloric acid solution, a saturated benzotriazole ethanol solution and anhydrous ethanol, efficient and accurate electrolytic etching of the metallographic structure of cobalt and cobalt-based alloy materials is achieved. The etching liquid can not only clearly show the microstructural characteristics of the material, but also effectively avoid the phenomenon of over-corrosion or under-corrosion, thereby greatly improving the observation quality and accuracy of the metallographic structure. The use of perchloric acid with a concentration of 70-72% ensures that the etching liquid has strong oxidation ability and stability, and can quickly and evenly corrode the sample surface. Using benzotriazole as an inhibitor can effectively control the corrosion rate, prevent excessive corrosion of the sample, and improve the controllability and safety of the corrosion process; at the same time, benzotriazole has good thermal stability, so that the corrosion effect of the etching liquid is less affected by temperature, and a good corrosion effect can be achieved at 0-60°C. Anhydrous ethanol is used as a solvent, which not only helps to evenly mix the components, but also improves the stability and environmental protection of the etching liquid. The metallographic etching method provided by the invention has simple and clear steps and is easy to operate. During the electrolytic corrosion process, by controlling parameters such as voltage, time and temperature, the corrosion process can be precisely controlled, thereby obtaining an ideal metallographic structure observation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which: Figure 1 The metallographic structure diagram of Example 1 is shown; Figure 2 The metallographic structure diagram of Comparative Example 1 is shown; Figure 3The metallographic structure diagram of Example 2 is shown; Figure 4 The metallographic structure diagram of Comparative Example 2 is shown; Figure 5 The metallographic structure diagram of Example 3 is shown; Figure 6 The metallographic structure diagram of Comparative Example 3 is shown. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example 1

[0016] Cut a high-purity cobalt target sample of appropriate size to be observed, and use 600, 1000, and 2000 mesh silicon carbide sandpaper to grind the sample step by step. Use water as a wetting agent during grinding. After grinding, rinse the sample surface. Then use a 1.5 μm diamond polishing agent to polish the sample. The polishing time is 5 min and the speed is 300 r / min. Add the metallographic structure electrolytic corrosion liquid of cobalt and cobalt-based alloy to the electrolytic cell, put the polished sample into the electrolytic corrosion liquid, stir, and the stirring speed is 5 r / s; connect the DC power supply for electrolytic corrosion, the voltage of the electrolytic corrosion is 14 V, the corrosion time is 30 s, and the temperature is 0°C. Rinse the corroded sample, blow dry with cold air or dry in an oven, and observe it with a metallographic microscope. The metallographic structure diagram is shown in the attached figure. Figure 1 shown.

[0017] In this embodiment, the electrolytic corrosion solution includes perchloric acid, benzotriazole and anhydrous ethanol, the volume ratio of the perchloric acid solution, the saturated benzotriazole ethanol solution and the anhydrous ethanol is 30:0.2:69.8, and the concentration of the perchloric acid solution is 70%. Example 2

[0018] Cut a high-purity cobalt target sample of appropriate size to be observed, and use 600, 1000, and 2000 mesh silicon carbide sandpaper to grind the sample step by step. Use water as a wetting agent during grinding. After grinding, rinse the sample surface. Then use a 1.5 μm diamond polishing agent to polish the sample. The polishing time is 5 min and the speed is 300 r / min. Add the metallographic structure electrolytic corrosion liquid of cobalt and cobalt-based alloy to the electrolytic cell, put the polished sample into the electrolytic corrosion liquid, stir, and the stirring speed is 5 r / s; connect the DC power supply for electrolytic corrosion, the voltage of the electrolytic corrosion is 14 V, the corrosion time is 30 s, and the temperature is 25°C. Rinse the corroded sample, blow dry with cold air or dry in an oven, and observe it with a metallographic microscope. The metallographic structure diagram is shown in the attached figure. Figure 3 shown.

[0019] In this embodiment, the electrolytic corrosion solution includes perchloric acid, benzotriazole and anhydrous ethanol, the volume ratio of the perchloric acid solution, the saturated benzotriazole ethanol solution and the anhydrous ethanol is 30:0.2:69.8, and the concentration of the perchloric acid solution is 71%. Example 3

[0020] Cut a high-purity cobalt target sample of appropriate size to be observed, and use 600, 1000, and 2000 mesh silicon carbide sandpaper to grind the sample step by step. Use water as a wetting agent during grinding. After grinding, rinse the sample surface. Then use a 1 μm diamond polishing agent to polish the sample. The polishing time is 10 min and the speed is 200 r / min. Add the metallographic structure electrolytic corrosion liquid of cobalt and cobalt-based alloy to the electrolytic cell, put the polished sample into the electrolytic corrosion liquid, stir, and the stirring speed is 2 r / s; connect the DC power supply for electrolytic corrosion, the voltage of the electrolytic corrosion is 12 V, the corrosion time is 20 s, and the temperature is 60°C. Rinse the corroded sample, blow dry with cold air or dry in an oven, and observe it with a metallographic microscope. The metallographic structure diagram is shown in the attached figure. Figure 5 shown.

[0021] In this embodiment, the electrolytic corrosion solution includes perchloric acid, benzotriazole and anhydrous ethanol, the volume ratio of the perchloric acid solution, the saturated benzotriazole ethanol solution and the anhydrous ethanol is 20:0.5:79.5, and the concentration of the perchloric acid solution is 72%.

[0022] Comparative Example 1 The difference between this comparative example and Example 1 is that the electrolytic etching solution includes ethanol, n-butanol, water, nitric acid and hydrofluoric acid, and the volume ratio of ethanol, n-butanol, water, nitric acid and hydrofluoric acid is 66:11:33:15:15. The electrolysis time is 20 s and the electrolysis voltage is 35 V. The metallographic structure diagram is shown in the attached figure. Figure 2 shown.

[0023] Comparative Example 2 The difference between this comparative example and Example 2 is that the electrolytic etching solution includes ethanol, n-butanol, water, nitric acid and hydrofluoric acid, and the volume ratio of ethanol, n-butanol, water, nitric acid and hydrofluoric acid is 66:11:33:15:15. The electrolysis time is 20 s and the electrolysis voltage is 35 V. The metallographic structure diagram is shown in the attached figure. Figure 4 shown.

[0024] Comparative Example 3 The difference between this comparative example and Example 3 is that the electrolytic etching solution includes ethanol, n-butanol, water, nitric acid and hydrofluoric acid, and the volume ratio of ethanol, n-butanol, water, nitric acid and hydrofluoric acid is 66:11:33:15:15. The electrolysis time is 20 s and the electrolysis voltage is 35 V. The metallographic structure diagram is shown in the attached figure. Figure 6 shown.

[0025] The invention provides a metallographic structure electrolytic etching liquid of cobalt and cobalt-based alloy and a metallographic etching method thereof. By accurately proportioning a perchloric acid solution, a saturated benzotriazole ethanol solution and anhydrous ethanol, efficient and accurate electrolytic etching of the metallographic structure of cobalt and cobalt-based alloy materials is achieved. The etching liquid can not only clearly show the microstructural characteristics of the material, but also effectively avoid the phenomenon of over-corrosion or under-corrosion, thereby greatly improving the observation quality and accuracy of the metallographic structure. The use of perchloric acid with a concentration of 70-72% ensures that the etching liquid has strong oxidation ability and stability, and can quickly and evenly corrode the sample surface. Using benzotriazole as an inhibitor can effectively control the corrosion rate, prevent excessive corrosion of the sample, and improve the controllability and safety of the corrosion process; at the same time, benzotriazole has good thermal stability, so that the corrosion effect of the etching liquid is less affected by temperature, and a good corrosion effect can be achieved at 0-60°C. Anhydrous ethanol is used as a solvent, which not only helps to evenly mix the components, but also improves the stability and environmental protection of the etching liquid. The metallographic etching method provided by the invention has simple and clear steps and is easy to operate. During the electrolytic corrosion process, by controlling parameters such as voltage, time and temperature, the corrosion process can be precisely controlled, thereby obtaining an ideal metallographic structure observation effect.

[0026] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.

Claims

1. A metallographic electrolytic etching solution for cobalt and cobalt-based alloys, characterized in that: The invention comprises perchloric acid, benzotriazole and anhydrous ethanol; the volume ratio of the perchloric acid solution, the saturated benzotriazole ethanol solution and the anhydrous ethanol is (20-30): (0.2-0.5): (69.5-79.8), and the concentration of the perchloric acid solution is 70-72%.

2. The electrolytic etching solution for metallographic structure of cobalt and cobalt-based alloys according to claim 1, characterized in that: The purity of the anhydrous ethanol is ≥99%.

3. A metallographic etching method using the metallographic structure electrolytic etching solution of cobalt and cobalt-based alloys according to any one of claims 1-2, characterized in that: The following steps are involved: (1) Cut a cobalt or cobalt-based alloy sample of appropriate size to be observed, grind the sample step by step using silicon carbide sandpaper, and then polish the sample using diamond polishing agent; (2) Adding a metallographic electrolytic corrosion solution of cobalt and cobalt-based alloy into an electrolytic cell, placing the polished sample into the electrolytic corrosion solution, stirring, and connecting a DC power supply for electrolytic corrosion. The voltage of the electrolytic corrosion is 12-14 V, the corrosion time is 20-30 s, and the temperature is 0-60°C; (3) Rinse the corroded sample, blow dry with cold air or dry in an oven, and observe it using a metallographic microscope.

4. The metallographic corrosion method of cobalt and cobalt-based alloy according to claim 3, characterized in that: In step (1), 600, 1000, and 2000 mesh silicon carbide sandpapers are used for step-by-step grinding.

5. The metallographic corrosion method of cobalt and cobalt-based alloy according to claim 3, characterized in that: In step (1), the sample is polished using a diamond polishing agent with a coarseness of 1-1.5 μm, the polishing time is 5-10 min, and the polishing speed is 200-300 r / min.

6. The metallographic corrosion method of cobalt and cobalt-based alloy according to claim 3, characterized in that: In step (2), the stirring speed is 2-5 r / s.

Citation Information

Patent Citations

  • Metallographic structure electrolytic solution, corrosion method of cobalt and display method of cobalt metallographic structure

    CN102443840B

  • Metallographic erosion method for displaying cobalt-chromium alloy structure

    CN102980794A

  • Metallographic structure electrolytic solution, corrosion method of cobalt and display method of cobalt metallographic structure

    CN102443840A

  • Electrochemical polishing electrolyte and polishing method for titanium and titanium alloy

    CN106567122A

  • FeCoNiCrMnAl high-entropy alloy electrolytic corrosion electrolyte and metallographic structure display method thereof

    CN111982641A